Human Gingival CD14(+) Fibroblasts Primed with Gamma Interferon Increase Production of Interleukin-8 in Response to Lipopolysaccharide through Up-Regulation of Membrane CD14 and MyD88 mRNA Expression - Tamai, Riyoko (American Society for Microbiology, 2002)
Gamma interferon (IFN-γ)-primed human gingival fibroblasts (HGF) have been shown to produce higher levels of interleukin-8 (IL-8) upon stimulation with bacterial products and inflammatory cytokines than nonprimed controls. In this study, we examined whether priming of HGF with IFN-γ up-regulates IL-8 production by the cells in response to purified lipopolysaccharide (LPS). The priming effect of IFN-γ was clearly observed in the high-CD14-expressing (CD14(high)) HGF but not in the low-CD14-expressing (CD14(low)) HGF. The CD14(high) HGF were most effectively primed with IFN-γ (1,000 IU/ml) for 72 h. To elucidate the mechanism of the priming effects of IFN-γ for the LPS response by HGF, we examined whether IFN-γ regulated expression of CD14, Toll-like receptor 2 (TLR2), TLR4, MD-2, and MyD88, all of which are molecules suggested to be associated with LPS signaling. In CD14(high) HGF, IFN-γ markedly up-regulated CD14 and MyD88 but not TLR4 protein and MD-2 mRNA expression, while in CD14(low) HGF, IFN-γ slightly increased MyD88 and scarcely affected CD14, TLR4 protein, and MD-2 mRNA levels. LPS-induced IL-8 production by IFN-γ-primed CD14(high) HGF was significantly inhibited by monoclonal antibodies (MAbs) against CD14 and TLR4, but not by an anti-TLR2 MAb. These findings suggested that IFN-γ primed CD14(high) HGF to enhance production of IL-8 in response to LPS through augmentation of the CD14-TLR system, where the presence of membrane CD14 was indispensable for the response of HGF to LPS.